2020
DOI: 10.1186/s12889-019-8140-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of psychosocial and perceived environmental factors with park-based physical activity among elderly in two cities in China and Germany

Abstract: Background: Urban parks play an important role in promoting physical activity (PA) among adults and especially among older city residents. According to the socioecological approach the association of physical environments and psychosocial factors in the context of park-based PA of elderly have not been systematically examined until now, let alone the relevance of the city (urban area) on a cross-cultural level. This study investigated selected aspects of (1) the association of psychosocial and park environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Physical activity is a modifiable factor which can be promoted for primary prevention. The number of parks in urban cities is positively associated with physical activity [ 33 ], better psychological health, and a cleaner environment while park-based physical activity is negatively associated with park distance [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity is a modifiable factor which can be promoted for primary prevention. The number of parks in urban cities is positively associated with physical activity [ 33 ], better psychological health, and a cleaner environment while park-based physical activity is negatively associated with park distance [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This green exposure impacts the population’s motivation and is associated with greater engagement in walking or other physical activities in Hong Kong [ 40 ]. Studies have demonstrated that street greenery, especially the parks in the city, contributes to the walking time and physical activity of older adults in Hong Kong [ 41 , 42 ]. Participants in our study tended to be at an earlier stage in their journeys to aging compared to older adults from other countries and areas (who were eligible for the assessment settings of our study).…”
Section: Discussionmentioning
confidence: 99%
“…Second, there were 19 evaluation index factors. The Likert method was used to evaluate the index 26 , and the answers each had five levels: very satisfied, satisfied, average, dissatisfied and very dissatisfied.…”
Section: Methodsmentioning
confidence: 99%